Kebijakan Manajemen Peningkatan Mutu Berbasis Sekolah - * Ngadimun (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2012)
Among the various educational problems faced by the Indonesian people is the low quality of education at all levels and units of education, especially primary and secondary education. Based on this fact, the efforts undertaken by the Government of South Kalimantan Province is doing a reorientation of education, namely the quality improvement-based management center to the management of school-based quality improvement. This study used a qualitative approach and the results describe that; effectiveness of policy implementation in the city of Banjarmasin MPMBS achieved in accordance with the objectives of the policy MPMBS improve the qualif of education by making changes to the educational management from the old pattern toward the pattern of MBS. Effectiveness is achieved because the policy MPMBS interpreted positively, then do MPMBS policy socialization through various media, and the availability of supporting resources policy. Factors that support the effectiveness of policy implementation in the city of Banjarmasin MPMBS among others: (a) has been implemented in earnest owned school autonomy, (b) community participation, (c) a democratic school leadership; transparency and accountability, (d) a conducive school environment, and (e) budgetary support from government and society. While inhibiting factors in the process of policy implementation in the city of Banjarmasin MPMBS among others: (a) the low quality of teachers according to minimum standards of education services, (b) the limitations of learning resources and learning media, and (c) bureaucratic obstacles in the management of school finances. MPMBS effective model is a management model that gives greater autonomy to schools and encourage community participation and community schools to improve the independence and quality of schools.Key Words : School-Based Quality Improvement Management